2016
DOI: 10.18632/oncotarget.13259
|View full text |Cite
|
Sign up to set email alerts
|

Roles of calpain-calpastatin system (CCS) in human T cell activation

Abstract: The immune response is determined by the speed of the T cell reaction to antigens assured by a state of readiness for proliferation and cytokine secretion. Proliferation, apoptosis and motion of many cell types are controlled by cytoplasmic proteases - μ- and m-calpain - and their inhibitor calpastatin, together forming the “calpain-calpastatin system” (CCS), assumed to modify their targets only upon activation-dependent cytoplasmic Ca2+ increase. Contrastingly to this notion, using quantitative real time PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Our further, as yet unpublished data indicate that this reduction in calpain amounts and activities is common also for other peripheral immune cells, including monocytes and NK cells. On the other hand we have shown that inhibition of calpains in the resting T cells leads to their decreased proliferation, cytokine secretion, and activation in relation to changed levels of activation of some molecules important for T cell signal transduction, including phospholipase C gamma, p56Lck, NFκB, and ZAP-70, all of which were earlier demonstrated to be affected by aging [ 88 , 89 ].…”
Section: Immune System Aging – Basicsmentioning
confidence: 99%
“…Our further, as yet unpublished data indicate that this reduction in calpain amounts and activities is common also for other peripheral immune cells, including monocytes and NK cells. On the other hand we have shown that inhibition of calpains in the resting T cells leads to their decreased proliferation, cytokine secretion, and activation in relation to changed levels of activation of some molecules important for T cell signal transduction, including phospholipase C gamma, p56Lck, NFκB, and ZAP-70, all of which were earlier demonstrated to be affected by aging [ 88 , 89 ].…”
Section: Immune System Aging – Basicsmentioning
confidence: 99%
“…Conventional calpains are localized to the majority of vascular systems, including veins 15 ) , arteries 16 ) and capillaries 17 ) , and are also expressed in ECs 16 , 18 ) , vascular smooth muscle cells (VSMCs) 19 ) and adventitial fibroblasts 20 ) . In addition to the vascular component cells, calpains are localized to immune cells 21 , 22 ) , which can be recruited into blood vessels in response to inflammatory insults. In addition to the conventional calpain isozymes, calpastatin, an endogenous calpain inhibitor, colocalizes with the proteases, and negatively regulates their proteolytic activity 12 14 ) .…”
Section: Vascular Calpain Systemsmentioning
confidence: 99%
“…Cal-pain1 (m-calpain) and calpain-2 (m-calpain) are the best characterized and most ubiquitously expressed calpains, and are activated by micromolar and millimolar calcium concentrations, respectively. Calpains belong to a family of calcium-dependent cysteine proteases with at least 16 members and are widely distributed in cells, including immune cells 61 and vascular cells. 62 They can be detected in multiple subcellular organelles, including mitochondria.…”
Section: Discussionmentioning
confidence: 99%